Diameters of certain classes of analytical functions. I - Vakarchuk , S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In the spaces of analytic functions E_q (Ω), q≥1, introduced by V. I. Smirnov, where Ω is a bounded simply connected domain in the plane C with sufficiently smooth boundary γ, we obtain order estimates of diameters of the classes W^rE_p (Ω) (р≥1, and r is a natural number ≥ 2) for distinct p and q.